Revisiting determinants of financial performance: The roles of environmental performance, environmental costs, and environmental disclosure - Sarwendhi, Rezza Arlinda; Dwiati, Agustina Ratna; Nita, Riski Aprilia; Febita, Gyzza (Privietlab, 2026)
This study seeks to analyze the impact of environmental performance, environmental costs, and environmental disclosure on the financial performance of consumer cyclical companies. The sample companies selected are cyclical companies with public status (Tbk) between 2019 and 2023. Sample selection was performed using the purposive method, and the final sample comprised 16 companies with 67 observations after outlier removal. The PROPER rating is used as a proxy to assess environmental performance, environmental costs are assessed through CSR expenditure disclosures in annual reports, and environmental disclosure is evaluated using GRI-G4 indicators. The analytical techniques employed included descriptive statistics and classical assumption tests. In addition, multiple regression models were used, and SPSS was used for hypothesis testing. Testing revealed that environmental performance negatively affects financial performance. This indicates that efforts to improve environmental performance require substantial costs, potentially reducing profitability. Meanwhile, environmental costs have no significant effect on financial performance, suggesting that increased CSR spending does not directly enhance profitability. Conversely, environmental disclosure positively impacts financial performance, implying that transparent reporting of environmental activities enhances public trust and investor perception. Some limitations of this study were the small number of companies used as samples because only a few companies participated in the PROPER rating or disclosed sustainability reports, and the need to remove outliers. Further research is expected to increase the number of samples, include additional independent variables, and examine other industry sectors to obtain more comprehensive insights.